Antarctic planetary wave spectrum under different polar vortex conditions in 2019 and 2020 based on total ozone column data - A. Grytsai; G. Milinevsky; Yu. Andrienko; A. Klekociuk; Yu. Rapoport; O. Ivaniha (Ukrainian Antarctic Journal, 2022)
We examine the zonal wavenumber spectrum of planetary (Rossby) waves in the atmosphere above Antarctica in each of two contrasting years: in 2019, when there was a sudden stratospheric warming (SSW), and in 2020 when the Antarctic stratospheric vortex was unusually strong and long-lived. The ozone hole (OH) is developed over Antarctica in spring, and its state depends on disturbances of the stratospheric polar vortex by planetary waves (PW). Our analysis uses data on the distribution of the total ozone column from the Ozone Monitoring Instrument on the Aura satellite and ground-based measurements from the Dobson spectrophotometer at the Ukrainian Antarctic Akademik Vernadsky station in Antarctica. The 2019 SSW strongly displaced the Antarctic vortex off-pole and aided the breakdown of the ozone hole. The SSW occurred during the peak activity of quasi-stationary planetary wave-1, which was enhanced at the time of the warming by the large amplitude of traveling wave-2. In the spring of 2020, the stratospheric polar vortex was relatively undisturbed, allowing the OH area to attain a size close to its historical maximum. A factor in 2020 that aided the stability of the vortex was the relatively small amplitude of wave-1. The stability was maintained despite regular periods when the amplitude of traveling wave-2 attained or even exceeded values around the time of the SSW in 2019. We find that a factor contributing to the differences between the wave effects in the two years is the dynamics of the quasi-stationary wave-1. Anticorrelation of the wave-1 and wave-2 amplitudes near the edge of the vortex was clearly observed in 2020, which can be caused by the transfer of planetary wave energy between different spectral wave components, unlike the situation in 2019.